Efektivitas Waktu Penyimpanan Sperma Ikan Komet (Carassium auratus auratus) dalam Larutan NaCl terhadap Derajat Pembuahan - Fia Sri Mumpuni; Yudi Pamoris (Paspalum: Jurnal Ilmiah Pertanian, 2011)
The research was conducted to determine the effect of storage time in 0.9% NaCl solution on sperm quality and the degree of fertilization goldfish, using a completely randomized design with 7 treatments consisting of sperm storage duration 0 hours, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, and 12 hours with 3 replications. The result showed that the goldfish sperm storage duration 2 hours still has a higher value of motility and the degree of fertilization. While the value of motility and the degree of fertilization lowest found in sperm storage duration of 12 hours. The deadlinefor sperm storage period goldfish 6 hours still have good motility value of 60% so it still possible for the process of fertilization and hatching.